EFFECT OF SALBUTAMOL SULFAT EXPOSURE TO THE SURFACE ROUGHNESS OF BIOACTIVE RESIN - Dewi Puspitasari; Diana Wibowo (FKG Unlam, 2021)
ABSTRACTBioactive composite resin is the newest restorative resin material which has good mechanical and aesthetic properties. In the oral cavity, the restoration is degraded due to exposure to acids, one of which is exposure to asthma drugs. Properties of composite resins that can be affected by degradation include surface roughness. This study aims to analyze salbutamol sulfate exposure to the surface roughness of bioactive resins. The research method used was pure experimental design with post test-only with control design. The study used 39 specimens of bioactive resin (8 mm in diameter and 2 mm in thickness), divided into 3 treatment groups, namely the 400µg salbutamol sulfate exposure group, the 800µg salbutamol sulfate exposure group and the artificial saliva control group with treatment every 24 hours for 7 days, subsequently the specimens are tested with the surface roughness of the composite resin using a surface roughness tester. The highest surface roughness value was found in the 800µg group (8.23 ± 0.98 µm), followed by 400 µg group (5.43 ± 1.16 µm) and the lowest in the artificial saliva group (2.63 ± 0.82 µm). There were significant differences in all treatment groups. The exposure of salbutamol sulfate affects the surface roughness of the bioactive composite resin, a higher number of exposure doses indicates a higher surface roughness value.Keywords: bioactive composite resins, salbutamol sulfate, surface roughness